Normal forces effects of a two in-wheel electric vehicle towards the human body - Nurul Afiqah, Zainal; Muhammad Aizzat, Zakaria; Baarath, Kunjunni; Abdul Majeed, Anwar P. P.; Ahmad Fakhri, Ab Nasir; Papaioannou, Georgios (Springer Science and Business Media Deutschland GmbH, 2022)
Traditionally, in order to comprehend the impact of vibration on human and vehicle ride comfort, past research often models the human biodynamic and vehicle models individually. Recent trends suggest that a better understanding of the behaviour could be achieved by fusing the models instead of analysing it separately. The present study evaluates the impact of the normal forces on specific parts of the human body. A human biodynamic model with five degrees of freedom is modelled together with a two in-wheel electric car model travelling at a speed of 10 km/h to investigate the effect of the normal forces. From the present investigation, it could be observed that the proposed model could highlight the impact of the normal forces on the body parts when the car is travelling either on a straight path or in taking corners.